PROBLEMA QIRÃ‚â€™Ã‚T DALAM AL-QURâ€™AN PERSPEKSTIF MUá¸¤AMMAD SHAá¸¤RÃ›R - Fauzi, Ahmad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2019)
The majority of Muslim scholars have agreed that al- QirÄâ€™Ät al-Sabá¿¾ or al- QirÄâ€™Ät al-â€˜Asyr is a á¹£aá¸¥á¿‘á¸¥ah (valid) and acceptable qirÄâ€™Ät. The variety in reading the Qurâ€™an is believed to be part of al-Aá¸¥ruf al-Sabá¿¾ah which was revealed to the Prophet Muhammad SAW. In contrast to this view, Muá¸¥ammad Syaá¸¥rÅ«r had analysed various kinds of qirÄâ€™ah through contemporary reading. Syaá¸¥rÅ«r indicated that there was an error that occured when giving syakal and iá¿¾rÄb to the texts of al-Tanzá¿‘l al-á¸¤aká¿‘m the HolyQurâ€™an. He justified that the error was ocured due to human error which then contributed greatly to the emergence of different pronunciation in the future. This study examines the perspective of Syahrur towards qirÄâ€™Ät, in which researcher have found that Syaá¸¥rÅ«râ€™s perspective about qirÄâ€™Ät is only assumption with lack of scientific evidence. Syaá¸¥rÅ«r has missed several aspects within his study towards parts of qirÄâ€™ah, for example the strict sanad lines through the history of a qirÄâ€™ah which was obtained through analytic descriptive and historical methods. There is also found that Syaá¸¥rÅ«râ€™s opinion was influenced by perspective of Western scholars (orientalists) who also doubted the authenticity of qirÄâ€™Ät, even though he did not explain this.Keywords: Muhammad Shahrur, qiraâ€™at, al-ahruf al-sabá¿¾ah, shakl.